Vernodalin Alleviates Cardiotoxicity and Inflammation in Isoproterenol-Mediated Myocardial Infarction through NF-κB/AMPK Signaling Pathways in Rats - Tao, Tao; Sun, Xiaona; Zhang, Tuowei; Vijayalakshmi, Annamalai; Niu, Fangqiao (Combinatorial Chemistry & High Throughput Screening, 2025)
BackgroundMyocardial infarction (MI) is the foremost cause of mortality in cardiovascular diseases. MI ultimately exacerbates cardiotoxicity due to the release of toxicity biomarkers and inflammatory infiltration.AimVernodalin (VN) is a renowned cytotoxic sesquiterpene lactone that possesses antioxidant, anticancer, and anti-inflammatory properties. The cardioprotective mechanism of VN remains concealed. Hence, we explored the cardioprotective efficacy of VN on isoproterenol (ISO)-mediated MI and analyzed its underlying mechanism.MethodsTo investigate the cardioprotective potential of VN (10 mg/kg bw), Wistar albino rats were subcutaneously injected with ISO (85 mg/kg bw) to induce MI. The assessment included measurements of heart weight/body weight index, hemodynamics, toxicity enzymes, histology, inflammatory mediators, and signaling pathway. While decreasing hemodynamic parameters and VEGF-B, AMPK, and eNOS signaling pathways, ISO increased heart weight/body weight index, cardiotoxicity enzymes, biomarkers, inflammation, and histological alterations.ResultsTreatment with VN could significantly (p<0.05) mitigate the heart weight/body weight index, cardiotoxicity enzymes, biomarkers, inflammatory cytokines, and histopathological changes while enhancing hemodynamic parameters and VEGF-B, AMPK, and eNOS signaling pathways. Collectively, our findings revealed that the VN ameliorated defensive action against MI and averted myocardial injury by reducing the NF-κB-mediated inflammatory pathways in rats.ConclusionThese findings established that VN expressively preserves the myocardium and employs anti-inflammatory actions by regulating NF-κB, VEGF-B, AMPK, and eNOS signaling pathways.
Keywords: isoproterenol